Peningkatan Hasil Belajar Sosiologi Dengan Model Pembelajaran Round Club - Midi Intan Elsioni Nenotek (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2024)
This research aims to improve sᴏsiᴏlᴏgi learning outcomes and improve sᴏsiᴏlᴏgi learning outcomes. The type of research used is classroom action research (PTK), which is intended to enhance classroom learning. The subjects in this research were 25 class XC students. The research was conducted in two cycles. Where in each cycle, there are 2 meetings, and at the end of the meeting, an evaluation or final test is held. The data collection techniques used were observation sheets, interviews, and tests. The data analysis techniques used are qualitative and quantitative data analysis. In the class action thesis from cycle I to cycle II, it was found that there was an increase in the learning outcomes of students in senior subjects after the Rund Club learning model was implemented in students’ classes. There was an increase in the percentage of students' learning outcomes, which was calculated from the average value of students in cycle I and cycle II, that in cycle I, the value obtained was 1,687 with an average of 67.48, categorized as sufficient, while in cycle II the value obtained was 1980 with an average of 79.2. In cycle II, students' classical learning mastery was achieved, and they experienced very good improvement. This result has reached the KKM determined in this research, namely 72.